Efficacy and Safety of Intraoperative Methylene Blue Dye for Sentinel Lymph Node Detection in Breast Cancer Surgery - Javed Iqbal Khan, Sadia Dilawer, Ayesha Tahir, Zeshan Mustafa, Akhtar Zaman, Sajad Ahmed, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Sentinel lymph node biopsy (SLNB) is the gold standard for axillary staging in early breast cancer. Although dual-agent mapping with radioisotopes and blue dye yields the highest detection rates, many centers lack access to nuclear medicine facilities. Methylene blue dye (MB) provides a cost-effective alternative. Objective: To evaluate the efficacy and safety of methylene blue dye for sentinel lymph node detection in breast cancer surgery. Methods: A prospective study was performed on 70 female patients with operable breast cancer. All underwent breast-conserving surgery or modified radical mastectomy with SLNB using methylene blue dye. Detection rate, number of sentinel nodes retrieved, histopathology, false-negative rate, and complications were recorded. Logistic regression was used to analyze predictors of SLN positivity. Results: The mean age of patients was 49.2 ± 10.4 years. SLN identification was successful in 94.3% of cases. The mean number of SLNs retrieved was 1.6 ± 0.8 per patient. Metastatic involvement was found in 21 patients (30%). The false-negative rate was 6.3%. Logistic regression revealed tumor size >2 cm and lymphovascular invasion as significant predictors of SLN positivity (p<0.05). Complications were minimal (2.8% tissue reactions, no severe allergic events). Conclusion: Methylene blue dye is a safe, reliable, and inexpensive method for SLN detection, achieving high detection rates and low complication rates. It represents a valuable technique in centers lacking access to radioisotopes. Keywords: Breast cancer, Sentinel lymph node biopsy, Methylene blue dye, Axillary staging, Lymphatic mapping.